The Khelipta Village and Its Scientist Saeed Al-Khelipty - Omar, Ardalan I. (Humanities Journal of University of Zakho, 2018)
The research aims to translate one of the media and a Kurdish character in April, in the age of Zangid and Ayyubids, that played a scientific and cultural role, the princes trusted and appointed him an educator and a teacher for their Alarbelaan children, which is known as the Ministry of Education, Saeed bin Saadallah Klapta emerged role in the field of poetry and literature. The nature of the subject demanded to divide this research into two parts, introduction and conclusion. The introduction was devoted to talking about Khilbta village form a geographical aspect, as for the second part (conclusion), it was devoted to talking about Sa`id Khiblti`s name, lineage, growth and education, period, his teachers and Skeikhs (religious men), an extract of his poetry and his death.